Human hearing enhanced by noise - Zeng, Fan-Gang; Fu, Qian-Jie; Morse, Robert (Brain research, 2000)
Noise was traditionally regarded as a nuisance, which should be minimized if possible. However, recent research has shown that addition of an appropriate amount of noise can actually improve signal detection in a nonlinear system, an effect called stochastic resonance. While stochastic resonance has been described in a variety of physical and biological systems, its functional significance in human sensory systems remains mostly unexplored. Here we report psychophysical data showing that signal detection and discrimination can be enhanced by noise in human subjects whose hearing is evoked by either normal acoustic stimulation or electric stimulation of the auditory nerve or the brainstem. Our results suggest that noise is an integral part of the normal sensory process and should be added to auditory prostheses.